Behavioral Modeling of RF Power Amplifiers Using Reduced Sampling Rate - Abdelnaby, Moustafa Farag (2018)
A Master of Science thesis in Electrical Engineering by Moustafa Farag Abdelnaby entitled, “Behavioral Modeling of RF Power Amplifiers Using Reduced Sampling Rate”, submitted in November 2018. Thesis advisor is Dr. Oualid Hammi. Soft and hard copy available.